Pemrograman Mikrokontroler Guna Memperkenalkan Industri 4.0 di SMA Negeri 7 Tangerang Selatan - Meyhart Bangkit Sitorus; Juara Mangapul; Hastuti Aziz; Tri Pramono; Pawenary IPM; Albert Gifson (Terang, 2019)
Today, technology is growing very fast and science in Information and Communication Technology (ICT) is still the main topic. The entry of the internet era created Industry 4.0 which is currently being developed by scientists to facilitate human life. Required several fields of science needed to develop Industry 4.0, one of which is programming. The problems obtained by high school students after graduating and then entering college in engineering, especially those majoring in Electrical Engineering are they have just come to know programming. This is due to the elimination of ICT subjects at the high school level since the implementation of the 2013 curriculum. Because high school graduates have no provision in engineering, few also want to improve their education in engineering. This PKM activity is a programming training that becomes the knowledge base for developing Industry 4.0. The training was focused on microcontoler programming using Arduino Uno as a learning medium. At the end of the activity, students were given a questionnaire containing five Likert scales to evaluate how effective the training was conducted. The training was attended by thirty nine students of South Tagerang 7 State High School who were in accordance with the grade XI majoring in science and interested in computer assistance. After the training, the results of the questionnaire concluded that participants "Agree" 61.53% and "Strongly Agree" 33.33% that this training increased their insight into Industry 4.0. The "Strongly Agree" Participant was 43.58% and "Agree" 33.33% that he was interested in exploring the Arduino Microcontroller. Participants "Strongly Agree" 43.58% and "Agree" 41.02% that they want additional lessons on the microcontroller at their school